TOMATO PEST TUTA ABSOLUTA IN TERMEZ DISTRICT OF SURKHANDARYA REGION. POPULATION-GENETIC MONITORING AND ECONOMIC SIGNIFICANCE (International conference on multidisciplinary science, 2025)
Tomatoes are the most consumed type of vegetables.  A number of insects cause serious damage to tomatoes.  Among them, the tomato moth is considered a serious p est of leaves and fruits.  This article describes the effectiveness of drugs used against tomato moth.